2008
DOI: 10.1242/dev.015867
|View full text |Cite
|
Sign up to set email alerts
|

Drosophilafragile X mental retardation protein developmentally regulates activity-dependent axon pruning

Abstract: Fragile X Syndrome (FraX) is a broad-spectrum neurological disorder with symptoms ranging from hyperexcitability to mental retardation and autism. Loss of the fragile X mental retardation 1 (fmr1) gene product, the mRNA-binding translational regulator FMRP, causes structural over-elaboration of dendritic and axonal processes, as well as functional alterations in synaptic plasticity at maturity. It is unclear, however, whether FraX is primarily a disease of development, a disease of plasticity or both: a distin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
269
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(294 citation statements)
references
References 92 publications
24
269
0
1
Order By: Relevance
“…Prior studies at the Drosophila neuromuscular junction have strongly indicated presynaptic functions for dFmr1 and translational control but have also pointed to their significant postsynaptic involvement in neuromuscular junction maturation, growth, and plasticity (75,76). More direct studies of experienceinduced long-term plasticity have been performed in the context of Drosophila olfactory associative memory, wherein a specific dFmr1 isoform in particular and translational control in general are necessary for long-term forms of memory (16,44).…”
Section: Multiple Synaptic Sites For Translational Control Necessary mentioning
confidence: 99%
“…Prior studies at the Drosophila neuromuscular junction have strongly indicated presynaptic functions for dFmr1 and translational control but have also pointed to their significant postsynaptic involvement in neuromuscular junction maturation, growth, and plasticity (75,76). More direct studies of experienceinduced long-term plasticity have been performed in the context of Drosophila olfactory associative memory, wherein a specific dFmr1 isoform in particular and translational control in general are necessary for long-term forms of memory (16,44).…”
Section: Multiple Synaptic Sites For Translational Control Necessary mentioning
confidence: 99%
“…These reports have provided considerable insight into the mechanism that might underlie abnormal synapse development and dendritic spine morphology in FXS. In Drosophila, FMRP is essential for synapse formation and experience-dependent axonal pruning during development (Gatto and Broadie, 2008;Tessier and Broadie, 2008). Studies in Fmr1 KO mice have further revealed that FMRP regulates protein synthesis-dependent axon pruning, dendritic spine elimination, and actin-dependent stabilization of spines.…”
Section: Abnormal Dendritic Spine Morphology In Fxsmentioning
confidence: 99%
“…Evidence from FXS Drosophila and mouse models suggests that calcium signaling is disturbed in the absence of FMRP, which could partially account for defects in neuronal network formation (Meredith et al, 2007;Tessier and Broadie, 2008). Furthermore, a recent report proposed a role for FMRP in retinoic acid-mediated homeostatic plasticity, an important signaling pathway regulating network activity (Soden and Chen, 2010).…”
Section: Altered Neuronal Network Formation In Fxsmentioning
confidence: 99%
“…Various intrinsic factors have been identified to regulate the pruning of axons and dendrites in Drosophila. These include the ubiquitin-proteosome system (Kuo et al 2006;Watts et al 2003), regulators of cytoskeletal dynamics (Billuart et al 2001;Lee et al 2009), caspase activities , transcription factors (Parrish et al 2007), RNAbinding proteins (Hoopfer et al 2008), proteins that hold sister chromatids together (Schuldiner et al 2008), and the FMRP protein disrupted in fragile X mental retardation (Tessier and Broadie 2008). Notably, molecular mechanisms involved in axon pruning in Drosophila share similarities with Wallerian degeneration in vertebrates.…”
Section: Guidance Molecules In Axon Pruning Intrinsic and Extrinsic Fmentioning
confidence: 99%